Máximo número de zeros de uma família de polinômios em um produto cartesiano finito - Muñoz Herrera, Nicolás Fitzgerald (2020)
In this work, we present an upper bound for the number of zeros of a family of polynomials in a finite cartesian product and additionally we show an example that takes that upper bound turning that upper bound in a maximum. These results have been proven using algebraic and combinatorial tools. The main elements used to prove this result are the Hilbert's base theorem, the Groebner's bases, the Hilber's function, the generalization of Macaulay's theorem and the generalization of Wei's theorem. This work was mainly based on the texts Ideals, Varieties and Algorithms (Cox D.) and Generalized Hamming weights for linear codes (Wei V.K.).